Development and validation of an HPLC-MS/MS method with QuEChERS extraction using isotopic dilution to simultaneously analyze chlordecone and chlordecol in animal livers. (30th June 2018) - Saint-Hilaire, Maïlie; Inthavong, Chanthadary; Bertin, Thomas; Lavison-Bompard, Gwenaëlle; Guérin, Thierry; Fournier, Agnès; Feidt, Cyril; Rychen, Guido; Parinet, Julien
Highlights: Quick, Easy, Cheap, Effective, Rugged and Safe extraction method in liver samples. Liquid chromatography tandem mass spectrometry method analysis. Validated method according to NF V03-110 and the European Union guidelines. Application of the method to field-collected liver samples. Chlordecone metabolism can take place in liver of ruminant species. Abstract: A QuEChERS extraction method followed by HPLC-MS/MS analysis was developed to simultaneously analyze chlordecone and its metabolite chlordecol in animal livers. The overall method was validated with accuracy profiles according to the French Standard NF V03-110 and European Union guidelines. The validation was performed on bovine, ovine and porcine liver samples. Linearity, matrix effect, accuracy, within-laboratory repeatability, specificity, LOQ, Q/q relative ion intensities, and uncertainty were reported. Recoveries were between 70% and 120%. LOQs of 1.36 µg chlordecone kg −1 and 2.50 µg chlordecol kg −1 of fresh liver were found. Twelve contaminated livers of bovine, ovine and porcine origin from the French West Indies or samples from in vivo studies were analyzed. In these liver samples from contaminated animals, chlordecone was quantified at concentrations higher than the maximum residue limit and chlordecol in very low amounts in all the samples. In addition, these results confirm that chlordecone can be metabolized in ruminant species.